Complete genome sequence of Planococcus faecalis AJ003T, the type species of the genus Planococcus and a microbial C30 carotenoid producer - Kim, Jin Won; Choi, Bo Hyun; Kim, Jin Ho; Kang, Hyun Jun; Ryu, Hoon; Lee, Pyung Cheon (Journal of Biotechnology, 2018)
A novel type strain, Planococcus faecalis AJ003T, isolated from the feces of Antarctic penguins, synthesizes a rare C30 carotenoid, glycosyl-4,4ʹ-diaponeurosporen-4ʹ-ol-4-oic acid. The complete genome of P. faecalis AJ003T comprises a single circular chromosome (3,495,892 bp; 40.9% G + C content). Annotation analysis has revealed 3511 coding DNA sequences and 99 RNAs; seven genes associated with the MEP pathway and five genes involved in the carotenoid pathway have been identified. The functionality and complementation of 4,4ʹ-diapophytoene synthase (CrtM) and two copies of heterologous 4,4ʹ-diapophytoene desaturase (CrtN) involved in carotenoid biosynthesis were analyzed in Escherichia coli.
Keywords: Carotenoid biosynthesis; Carotenoids; Complementation; Complete genomes; Desaturase; Gene clusters; MEP pathways; Planococcus faecalis; Bacterial Proteins; Carotenoids; Genome, Bacterial; Planococcus Bacteria; Carotenoids; Complete genome sequence; Gene cluster; Planococcus faecalis